Digital Literacy Education as an Effort to Build a Generation of Technology-Savvy and Economically Independent Village Teenagers - Miswar, Edy; Siregar, M. Ridha; Ramadhan, Fakhri; Nisva, Raisa Ullya; Zikran, Ghrina; Humaira, Radhia; Maulana, Rizki; Saddaq, Mizan (Universitas Syiah Kuala, 2024)
The community service activity themed